Economic growth and subjective well-being: reassessing the easterlin paradox - Betsey Stevenson; Justin Wolfers (Institute for the Study of Labor (IZA), 2008)
The Easterlin paradox suggests that there is no link between a society's economic development and its average level of happiness. We re-assess this paradox analyzing multiple rich datasets spanning many decades. Using recent data on a broader array of countries, we establish a clear positive link between average levels of subjective well-being and GDP per capita across countries, and find no evidence of a satiation point beyond which wealthier countries have no further increases in subjective well-being. We show that the estimated relationship is consistent across many datasets and is similar to the relationship between subject well-being and income observed within countries. Finally, examining the relationship between changes in subjective well-being and income over time within countries we find economic growth associated with rising happiness. Together these findings indicate a clear role for absolute income and a more limited role for relative income comparisons in determining happiness.
urn:nbn:de:101:1-20080828153
Keywords: D6; 330; Happiness; subjective well-being; Easterlin Paradox; life satisfaction; economic growth; well-being-income gradient; hedonic treadmill; Lebenszufriedenheit; Lebensstandard; Wirtschaftswachstum; Sozialprodukt; Lebensqualität; Welt; Lebenszufriedenheit; Lebensstandard; Wirtschaftswachstum; Sozialprodukt; Lebensqualität; Welt